2017
DOI: 10.3171/2016.10.peds16279
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumors of the spine: a pediatric case report with a comprehensive review of the literature

Abstract: Solitary fibrous tumors of the spine are rare lesions. Their description in the literature is limited to case reports and small case series. While generally benign lesions, they can recur and occasionally occur as malignancies. Here the authors present the case of a 10-year-old boy, the youngest patient and first preadolescent reported thus far, with this condition. In addition, they perform a comprehensive review of all previously published cases of spinal solitary fibrous tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…Combining data from recent reviews, there are now 114 cases of spinal SFT/HPC that have been reported in the literature (82)(83)(84). About 10% of CNS lesions occur in the spine, usually in the intradural compartment, although extradural and even intramedullary locations have been reported.…”
Section: Solitary Fibrous Tumor/ Hemangiopericytomamentioning
confidence: 99%
“…Combining data from recent reviews, there are now 114 cases of spinal SFT/HPC that have been reported in the literature (82)(83)(84). About 10% of CNS lesions occur in the spine, usually in the intradural compartment, although extradural and even intramedullary locations have been reported.…”
Section: Solitary Fibrous Tumor/ Hemangiopericytomamentioning
confidence: 99%
“…ese can include the sinonasal tract, oral cavity, and orbit [13][14][15]. ere have also been cases of SFT arising from the extremities and bone as well as very few reported from the abdominal wall [16][17][18]. SFTs are most commonly benign, but 10-20% of cases have been reported to be malignant.…”
Section: Discussionmentioning
confidence: 99%
“…Solitary fibrous tumors can occur in various parts of the body, such as the thoracic cavity, the abdominal cavity, the pelvic cavity, the central nervous system, and the head, neck, and limbs. According to the data analysis of 804 patients over the past 40 years by the Surveillance, Epidemiology, and End Results (SEER) Program of the National Cancer Institute of the United States, patients with chest, abdominal, and pelvic cavity involvement accounted for 35.3% of cases, patients with central nervous system involvement accounted for 24.5%, and patients with head and neck or limb involvement accounted for 19.9% and 16.2%, respectively[ 6 ]. However, no previous study has reported cases of primary solitary fibrous tumors involving the pelvic ring.…”
Section: Discussionmentioning
confidence: 99%
“…One paper reviewed previous reports on 56 cases of spinal solitary fibrous tumors with follow-up results: among the 9 patients with subtotal resection, 5 experienced local recurrence in the 6-month to 21-year period following the surgery, and 1 had new spine lesions[ 12 18 ]. Among the 46 patients who received gross total resection, 41 (89.1%) did not experience recurrence[ 6 , 18 21 ]. For spinal solitary fibrous tumors, most tumors involved the dura mater, arachnoid tissue, and even the spinal cord[ 22 25 ], at which point wide resection and en bloc resection are often impossible.…”
Section: Discussionmentioning
confidence: 99%